2019
DOI: 10.1183/13993003.01402-2019
|View full text |Cite
|
Sign up to set email alerts
|

Nationwide analysis of treatment outcomes in children and adolescents routinely treated for tuberculosis in the Netherlands

Abstract: BackgroundAs a vulnerable population, children and adolescents with tuberculosis (TB) are faced with many challenges, even those who live in low TB incidence countries. We aimed to evaluate factors associated with TB treatment outcomes allowing more focused interventions to support this population once diagnosed.MethodsA retrospective cohort study using a nationwide surveillance database was performed in children and adolescents (aged 0–18 years) treated for TB in the Netherlands from 1993 to 2018. Logistic re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
12
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 33 publications
3
12
1
Order By: Relevance
“…However, clinical experience makes us suppose that the score parameters were taken into consideration by physicians at the time of TB diagnosis in children, although not registered in the medical records. We observed a high treatment success rate in the overall sample (85%), lower than that described by European countries (88-100%) (Abubakar et al, 2008;Ziemele et al, 2017;Gafar et al, 2019), but higher than that reported from some African countries (around 77%) (Flick et al, 2016;Wobudeya et al, 2017). The mortality rate in this study (1%) is comparable to the case fatality rate described by Jenkins et al in countries with low HIV prevalence (0.9%) (Jenkins et al, 2017).…”
Section: Discussionsupporting
confidence: 47%
“…However, clinical experience makes us suppose that the score parameters were taken into consideration by physicians at the time of TB diagnosis in children, although not registered in the medical records. We observed a high treatment success rate in the overall sample (85%), lower than that described by European countries (88-100%) (Abubakar et al, 2008;Ziemele et al, 2017;Gafar et al, 2019), but higher than that reported from some African countries (around 77%) (Flick et al, 2016;Wobudeya et al, 2017). The mortality rate in this study (1%) is comparable to the case fatality rate described by Jenkins et al in countries with low HIV prevalence (0.9%) (Jenkins et al, 2017).…”
Section: Discussionsupporting
confidence: 47%
“…After these improvements, we expect that the completeness of TB notification has increased over time. Although some EPTB cases such as abdominal TB, osteoarticular TB and urogenital TB could be life-threatening, these forms of EPTB were assumed to be less severe than CNS and miliary TB in our study because EPTB cases other than CNS and miliary TB were not associated with higher risk of mortality in our previous analysis [4]. In addition, this study is limited by its retrospective nature with partly incomplete records for some of the variables.…”
Section: Discussionmentioning
confidence: 91%
“…In low-and middle-income countries, ACF among household contacts of patients with TB is effective in enhancing TB case detection [41,42], and reducing all-cause mortality [41]. In the Netherlands, ACF interventions also benefit children and adolescents in improving TB treatment outcomes, particularly in reducing all-cause mortality [4]. However, it should be acknowledged that even in a setting where ACF is well implemented like the Netherlands, missed opportunities for prevention persist.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings on DILI in children with TBM warrant further investigation as DILI has clinical implications in increasing patient morbidity/mortality. 38 The risk of DILI with increased drug dosages requires consideration, but it should be balanced against the need to ensure optimal treatment of a life-threatening illness like TBM. 29 39 Combining therapeutic drug monitoring as a decisive tool for TB treatment, 40 and regular monitoring of LFTs, 19 might benefit to ensure drug efficacy without causing toxicity.…”
Section: Discussionmentioning
confidence: 99%